HIF2α activation and mitochondrial deficit due to iron chelation cause retinal atrophy - Yang Kong; Pei‐Kang Liu; Yao Li; Nicholas D Nolan; Peter M J Quinn; Chun‐Wei Hsu; Laura A Jenny; Jin Zhao; Xuan Cui; Ya‐Ju Chang; Katherine J Wert; Janet R Sparrow; et al. (EMBO Molecular Medicine)
Abstract Iron accumulation causes cell death and disrupts tissue functions, which necessitates chelation therapy to reduce iron overload. However, clinical utilization of deferoxamine (DFO), an iron chelator, has been documented to give rise to systemic adverse effects, including ocular toxicity. This study provided the pathogenic and molecular basis for DFO‐related retinopathy and identified retinal pigment epithelium (RPE) as the target tissue in DFO‐related retinopathy. Our modeling demonstrated the susceptibility of RPE to DFO compared with the neuroretina. Intriguingly, we established upregulation of hypoxia inducible factor (HIF) 2α and mitochondrial deficit as the most prominent pathogenesis underlying the RPE atrophy. Moreover, suppressing hyperactivity of HIF2α and preserving mitochondrial dysfunction by α‐ketoglutarate (AKG) protects the RPE against lesions both in vitro and in vivo. This supported our observation that AKG supplementation alleviates visual impairment in a patient undergoing DFO‐chelation therapy. Overall, our study established a significant role of iron deficiency in initiating DFO‐related RPE atrophy. Inhibiting HIF2α and rescuing mitochondrial function by AKG protect RPE cells and can potentially ameliorate patients' visual function.